The use of salt in fisheries product processing industry - Luthfi Assadad (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
Salt is one of the most important food materials for human life. Although the total consumptionof salt increases every year, the total production decreases. Salt, in Indonesia and other tropicalcountries, is manufactured by using total crystallization system with poor quality and low quantity.The shortcomings in salt production are its low productivity and the function alteration of salt farms.Improving the quality of salt needs to be done, for example by improving technology, qualitymanagement system, trainings, and equipments. Whereas its quantity could be improved byintensification and extensification. Salt is an industrial product and an important material for otherindustries. Fish processing industry, both traditional and modern, uses salt as product processingaid. Salt preserves flavour and enhances the appearance and texture of fish meat. Salt is used intraditional processing industries, to produce dried fish, boiled fish, and fermented fish products.Whereas in modern processing industry, salt is used for the manufacture of surimi products and itsderivatives.